The effect of gap between plastic leaded chip carrier (PLCC) using Computational Fluid Dynamic (CFD) Software, FLUENT - Mazlan Mohamed; Anizah Kalam; Huck-Soo Loo; A.M. Mustafa Al Bakri; M.S. Abdul Aziz; C.Y. Khor; Mohammad Amizi Ayob; Mohd Sukhairi Mat Rasat
This paper presents the effect of gap between Plastic Leaded Chip Carrier (PLCC) by using three dimensional numerical analysis of heat and fluid flow in computer. 3D model of microprocessors is built using GAMBIT and simulated using FLUENT software. The study was made for twomicroprocessors arranged in line under different types of inlet velocities and package (chip) powers. The results are presented in terms of average junction temperature and thermal resistance of each package. The junction temperature is been observed and it was found that the junction temperature of the microprocessors is not exceed 70º C. It also found that the gap between PLCC play important rolesto control and manage the junction temperature. The strength of CFD software in handling heat transfer problems is proved to be excellent.